Is “I am a man” a hinge certainty? On gender, antifoundationalism, and the possibility of changing a Weltbild - Pennycook, Pedro; Torres, Juliany; Silva, Marcos (Argumentos - Revista de Filosofia, 2025)
In On Certainty, Wittgenstein suggests that doubting whether he “is a man” may exceed the limits of how our epistemic language-games function (§79). Since the certainty that things like “men” and “women” exist in the world is so deeply embedded in our world-picture (Weltbild) that it cannot be called into question, it might constitute a curious example of what the author calls a “hinge certainty”. However, the fact that our worldview is shaped by gender-related certainties should not be taken as immutable. In this paper, we argue that even if the gender binary can be considered a hinge certainty, this does not prevent it from being challenged and changed. To do so, we first contend that any interpretation of how hinges structure our epistemic language-games must prioritize at least one of the metaphors presented in On Certainty over the others. The selected metaphors would support either an anti-foundationalist or foundationalist epistemological reading. A foundationalist view of hinge certainties, we argue, is responsible for their supposed immutability, including gender-related hinge certainties. We then take the presumed immutability of gender certainties as a specific case study concerning the alleged immutability of hinge certainties. Here, we propose interpreting the gender binary as the foundation of our world-picture, whose “certainty” can be seen as a violent normative constraint. Through our anti-foundationalist reading of Wittgensteinian epistemology, we maintain that hinge certainties must be mutable, given their functional status — that is, their role or function should vary across different contexts. In defense of revising hinge certainties, we argue that our practices can serve as tools to challenge the hinge status of the gender binary.